Moulding soft skills module for KUKTEM - Fatmawati, Latada (2005)
The research aims to identify the 'Soft Skills' needed by the industry, and how well our graduates are ready for the challenge. The research focused on five elements of 'Soft Skills' and the training method used by the industry to enhance their workers' skills. Fifty-five (55) Human Resource (HR) managers from industries around the East Coast, Klang Valley and Shah Alam industrial area are involved in the research. The HR managers were less than satisfied with the performance of their newly graduate workers in all aspects investigated; communication, team working, positive values, leadership, and learning capability. Nevertheless, it is suggested that among the five elements that we investigated, positive values, communication skills and team working are the most needed skills. The HR managers reported that college graduates' skills are not always adequate to perform the task required on the job. The research reveals an urgent need for additional teaching on how to express oneself more professionally, how to work with others, how to behave and finally, the need to expose our students to the reality of working environment and its demands.